Defining Tabayyun as a Psychological Attribute: Study of Thematical Exploration - Fathoni, Aryo Bima; Verina, Azti; Rahmah, Bilqisthi; Paiqotul, Nida; Ramdani, Zulmi (Universitas Muhammadiyah Surakarta, 2019)
Purpose: This research aims to explore and develop “Tabayyun” as a psychological concept that can be used to measure and prepare students to be responsive and preventive of all forms of information that come into their lives. Methodology: This study uses a qualitative approach to thematic analysis methods. Data is collected by distributing questionnaires, interviews and analysis of social media content. The questionnaire was distributed via Google form consisting of 4 questions for 14 days to 31 students of UIN Sunan Gunung Djati Bandung. Interview data collection was carried out for lecturers, police and religious teachers. In the analysis of social media content, researchers analysed the content of 8 video lecturer on Youtube.Results: Tabayyun is defined as “Behavior of checking, criticising, and clarifying information that is not yet correct and not in a hurry to spread the information.” In this study also found four aspects of Tabayyun; (1) Critical thinking, (2) self-control, (3) open-minded, and (4) information-seeking behaviour. Applications/Originality/Value: There is no previous research that explores the construct of Tabayyun from a psychological perspective. It is very important considering this construct is an important aspect of understanding the social psychological phenomena received by the subject in the era of globalisation. This research can also be a comprehensive framework for understanding human behaviour in the context of cyberpsychology